2012
DOI: 10.1002/nem.1810
|View full text |Cite
|
Sign up to set email alerts
|

Link repair in managed multi‐domain connections with end‐to‐end quality guarantees

Abstract: SUMMARY The Internet is a platform providing connection channels for various services. Whereas for services like email the best‐effort nature of the Internet can be considered sufficient, other services strongly depend on service‐specific connection quality parameters. This quality dependence has led to dedicated content distribution networks as a workaround solution for services like YouTube. Such workarounds are applicable to a small number of services only. With the global application of the Internet, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Authors define low-level inter-domain signalling protocols assuming that the upper layers of inter-domain relations have been resolved at a strategic and business level, allowing such automatic operations. With similar assumptions, Yampolskiy et al [12] propose methods for autonomic provision of end-to-end QoS guarantees for point-to-point links in a multidomain environment. Our experience in the GÉANT-NREN environment showed that such assumptions should not be taken as granted and that in loosely coupled federations (defined in the next section) there is a considerable objection towards deployment of a system in which service provisioning request initiated in one domain is automatically configured in remote domains.…”
Section: Related Workmentioning
confidence: 99%
“…Authors define low-level inter-domain signalling protocols assuming that the upper layers of inter-domain relations have been resolved at a strategic and business level, allowing such automatic operations. With similar assumptions, Yampolskiy et al [12] propose methods for autonomic provision of end-to-end QoS guarantees for point-to-point links in a multidomain environment. Our experience in the GÉANT-NREN environment showed that such assumptions should not be taken as granted and that in loosely coupled federations (defined in the next section) there is a considerable objection towards deployment of a system in which service provisioning request initiated in one domain is automatically configured in remote domains.…”
Section: Related Workmentioning
confidence: 99%